PENERAPAN SISTEM PEMBELAJARAN BERBASIS PRIVAT UNTUK MENINGKATKAN PEMAHAMAN NILAI NILAI AJARAN ISLAM DI DESA PERIA-RIA - Mafira Roza, Mafira Roza (STAI Nusantara Kota Banda Aceh, 2025)
This study aims to analyze the implementation of a private-based learning system to improve understanding of Islamic values ​​in Peria-Ria Village. The background of this research is based on the low level of understanding of Islamic teachings among some residents due to time constraints and learning methods in formal institutions. Through a personalized and flexible private learning approach, students have the opportunity to learn more in-depth and at their own pace. This method also allows for more intense interaction between teachers and students, allowing for a more effective instillation of Islamic values ​​such as faith, noble character, and social concern. The results of this system's implementation indicate an increase in understanding and application of Islamic values ​​in the daily lives of the Peria-Ria Village community.